Investigating the Impact of Cochlear Implants on Speech Perception and Quality of Life in Individuals with Profound Hearing Loss - Imran Khan, Aftab Ahmad, Asghar Ullah Khan, Izzah Islam, Maqbool Ahmed, Kamran Chaudhry (Pakistan Journal of Medical & Health Sciences, 2024)
Aim and objective: To investigate the impact of cochlear implants on speech perception and quality of life in individuals with profound hearing loss. Materials and Method: The current prospective study was conducted at Niazi Medical college Sargodha and Sudais hospital Charsadda the ENT department in tertiary care hospital from March 2022 to September 2023 after approval from the institutional review board. A total of 66 participants were selected through the purposive sampling technique irrespective of their age. The SF-36 along with an NCIQ were utilized to collect information on health-related quality of life Participants having CI were provided with a pair of copies of each HRQOL assessment and an explanation letter explaining the study goals. The first one catered to people in their before-CI state, whereas the second one catered to those who had already had CI. The HRQOL ratings, hearing evaluations, along with additional implant factors were analyzed. Results: A total of 166 participants were selected for the study of which 27 (40.90%) were male and 39 (59.09%) were female. The present mean age of participants was 48.64±12.7 years, while the age at the time of the implant was 44.23±13.4 years, moreover, their period of deafness was 12.42±8.2 years as well as, and their duration of the implant was 4±1.9 years. More importantly, 87.87% of them were satisfied with cochlear implants. The primary sound sensation before CI was 16.5 (13.7) and after the CI was 69.8 (15.3), however, the production of speech before the CI was 50.5 (22.6) and after the CI Was 82.7 (11.2). the advanced sound sensation pre-CI was 17.3 (15.6) and post-CI it was 68.2 914.2). Moreover, their social life interaction with the people was 34.2 (17.2), and after the CI was 69.2 (17.6). Conclusion: The current study concluded that a cochlear implant is a safe and successful procedure. More importantly, 87.87% of them were satisfied with cochlear implants. This NCIQ showed a positive correlation with speech and quality of life measurements, as well as the ability to recognize the substantial impacts of cochlear implants on health-related quality of life. Keywords: Cochlear implants, deafness, otosclerosis, HRQOL,